Ayurvedic Management of Congenital Elongation of Cervix- A Single Case Study (International Journal of Ayurveda and Pharma Research, 2021)
Elongation is one among the various congenital abnormalities of cervix, which is often one of the causes of primary infertility. The only available treatment is cervical amputation. The word yoni collectively refers to reproductive organs, however here it can be considered as the cervix. So elongated cervix can be correlated to Prasramsini Yoni Vyapat where there is laxity and descend of the cervix. All Acharyas have mentioned similar mode of treatment in case of Srasta Yoni which include Abhyanga, Sweda, Veshavara Bandha, Uttarabasti etc. A case report of patient presenting with congenital cervical elongation is being discussed here. In this case there was reduction in the elongation of the cervix by Veshavara Bandha and Uttarabasti with Jathyadi Taila. The drugs used in Veshavara Bandha were having Balya, Brimhana and Grahi properties which helped in reducing the length of the cervix significantly and preventing further elongation. Thus Ayurvedic management was found to be effective in elongation of cervix to an extent even though it cannot be cured completely.